2017
DOI: 10.16965/ijpr.2017.220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immediate Effect on Hamstring Flexibility Using Non Ballistic Active Knee Extension in Neural Slump Position and Static Stretch Technique

Abstract: Background: Amongst all of the biarticular muscles of the human body hamstring have a greater tendency to shorten. Increased tension in the neural structures has also been shown to be one of the most important causative factor for the hamstring tightness for which mobilisation of the nervous system has emerged as a significant adjunct apart from routine stretching techniques. There are lots of studies available which has proven the effect of stretching on the hamstring flexibility, but only after giving the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Thus there are many proposed mechanism of improvement of hamstring flexibility by neural slump position. But reduced mechanosensitivity is the chief mechanism by which the nervous system becomes more tolerant to source of pain with movements and postures [1] A similar study , examining the immediate effect of neurodynamic sliding technique verses mulligan's bent leg raise technique on hamstring flexibility in a symptomatic individuals by vinod babu et. Al found that , In NDST group, who received Neurodynamic sliding technique showed that there is a statistically significant change in means of passive SLR ROM, when means were analysed from pre intervention to post intervention measurements within the group with positive percentage of change showing there is increase in post means.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus there are many proposed mechanism of improvement of hamstring flexibility by neural slump position. But reduced mechanosensitivity is the chief mechanism by which the nervous system becomes more tolerant to source of pain with movements and postures [1] A similar study , examining the immediate effect of neurodynamic sliding technique verses mulligan's bent leg raise technique on hamstring flexibility in a symptomatic individuals by vinod babu et. Al found that , In NDST group, who received Neurodynamic sliding technique showed that there is a statistically significant change in means of passive SLR ROM, when means were analysed from pre intervention to post intervention measurements within the group with positive percentage of change showing there is increase in post means.…”
Section: Discussionmentioning
confidence: 99%
“…Group A Patients were then instructed to perform 30 repetitions of active knee extension maintaining the full dorsiflexion, upto the point where the firm resistance or stretch was felt at the posterior thigh, knee or calf and position was held for the self count of one, two, three, four by the patient The position was held for 6 seconds and 30 repetitions were done. [1] Group B While the subject was lying in supine position, the subject's hip was passively flexed and the leg extended until tension was sensed by the researcher and the subject reported a moderate stretching sensation. The subject provided a moderate knee flexion isometric contraction (approximately 50% of maximal contraction), by pressing his ankle joint against the top of the researcher's shoulder for 7-10 s. This was followed by 2-3 s of relaxation, and then the leg was passively stretched by the researcher to the palpated barrier and/or tolerance to stretch and held for 30 s. The leg was then lowered to the table for a short resting period (approximately 10 s).…”
Section: Group Amentioning
confidence: 99%
See 3 more Smart Citations